Self-Disclosure Of Generation Z Heavy Social Media Users In Bali - Sari, Wulan Purnama; Paramita, Sinta; Irena, Lydia (Universitas Islam Negeri Raden Intan Lampung, 2025)
The digital era keeps evolving, particularly in terms of communication technology and internet usage. It is predicted that around 80% of Indonesia's population will have social media accounts by 2026, with the majority of users being Generation Z. The close relationship between Generation Z. Social media has given rise to the term